1997
DOI: 10.1097/00003072-199709000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Regression of Focal Nodular Hyperplasia of the Liver After Oral Contraceptive Discontinuation

Abstract: There is uncertainty regarding the role, if any, of oral contraceptive steroids in the development of focal nodular hyperplasia of the liver. A case of focal nodular hyperplasia of the liver diagnosed by scintigraphy in a 33-year-old woman is presented. The lesion regressed in a dramatic way after oral contraceptive discontinuation. This case report suggests that oral contraceptives may influence the natural history of focal nodular hyperplasia of the liver, and that a trophic effect on the liver lesion is qui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Extensive sectioning of the liver at autopsy in the area of the previous FNH revealed fibrous scar tissue. Although uncommon, FNH regression has been reported 14, 15…”
Section: Discussionmentioning
confidence: 99%
“…Extensive sectioning of the liver at autopsy in the area of the previous FNH revealed fibrous scar tissue. Although uncommon, FNH regression has been reported 14, 15…”
Section: Discussionmentioning
confidence: 99%
“…Since the 1970s, many cases of FNH have been reported in patients taking both high- and low-dose OCPs. Some authors have suggested that OCPs are not the pathophysiologic cause of FNH (as in hepatic adenoma) ( 1 ); however, the correlation between regression of FNH lesions and the discontinuation of OCPs in several cases have suggested that exogenous estrogens may act as trophic agents ( 8 , 16 , 17 , 18 , 19 , 20 , 21 ). Some groups have argued that FNH may regress spontaneously, regardless of patients’ OCP use or endogenous hormonal status ( 10 , 13 , 14 , 22 , 23 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some groups have argued that FNH may regress spontaneously, regardless of patients’ OCP use or endogenous hormonal status ( 10 , 13 , 14 , 22 , 23 , 24 ). Others have posited that there is a direct association between OCP use and FNH ( 15 ), and that withdrawal of OCPs may lead to its regression ( 12 , 17 , 18 , 19 , 20 ). Several groups have reported data on the natural history of FNH, the highlights of which are summarized in Table 1.…”
Section: Discussionmentioning
confidence: 99%